Chiesa e memoria - Bruguès, Jean-Louis (Alpha Omega, 2016)
Summary: The cohesion of a social, political or religious group, and even more its future, depend in large part upon its capacity to preserve the memory of its own origins. Indeed, in regard to its Founder, Christianity operates four kinds of memory: that of the places in which it has been lived, that of the closeness (or proximity), drawing close to those who have drawn close to it, sacramental memory, which transmits the very life of the risen Christ, and finally the memory of the writings which treat of Christ in his time in the midst of people and of the Church sent out on mission. The Vatican Library, then, is a treasure for the Church and for the whole of humanity. Even in secularised societies and in a certain way especially in such settings, precisely because they are more disposed to cancel the past, the Church has become the guardian of memory. This is particularly true in our times, in which, since 1968, for the first time in modern history, a generation has decided to make tabula rasa of the past.Key words: memory, Church, memory of Christ, Vatican Library, guardian of memory.